Discourse - Pragmatic Analysis of Hijab Fashion Bloggers in Fustany Magazine - Qasim, Sawsan Abdul-Munem (Mahesa Research Center, 2023)
With women's growing desire to wear the hijab and the growth of Islam over the world, hijab fashion has emerged during the twentieth century, and there are now more hijab fashion magazines than ever before. In addition to the media's function and the advancement of technology, one may easily purchase clothing from online stores. This study has two goals, first: the discourse cohesiveness of the hijab fashion advertisements in Fustany magazine, as well as the grammatical and semantic relationships within the texts, as one of the designers' persuasive strategies for attracting clients. The researcher adopts the analytical framework proposed by Halliday and Hasan in 1976. The second part of this study looks at certain fashion bloggers' pragmatic speech actions. Based on data analysis, the study has demonstrated that repetition and other linguistic devices are frequently employed by advertisers to draw customers' attention to their offerings and improve brand recognition. As a technique for promoting advertisements, commissives are often utilized, along with other sorts of assertives and directives.